Bacteremia caused by Comamonas kerstersii in a patient with acute perforated appendicitis and localized peritonitis: case report and literature review - Zhang, Yingmiao; Li, Kun; Zhan, Yu; Shi, Lifeng; Zeng, Yi; Wang, Hui; Lu, Zhongxin (Frontiers in Medicine, 2023)
Comamonas kerstersii (C. kerstersii) is a Gram-negative bacterium that was initially thought to be non-pathogenic to humans and is abundant in the environment.In recent years, with the availability of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) that enable fast and accurate bacterial identification, there have been increasing number of reports of human infections caused by C. kerstersii, indicating that this organism has emerged as human pathogen. In fact, most clinical isolates of C. kerstersii are recovered from peritoneal liquid, and bacteremia has been infrequently reported. Here, we report a case of bacteremia caused by C. kerstersii in a 28-year-old male patient with acute perforated appendicitis and localized peritonitis and present a comprehensive review of C. kerstersii infections in pathogenic diagnosis and clinical treatment as well as prognosis, thus providing a better understanding of C. kerstersii-related infections.